2016
DOI: 10.1002/eji.201646708
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis: A tale of two distinct pathomechanisms that make you itch

Abstract: Atopic dermatitis (AD) or eczema is the most common chronic inflammatory skin disease, with an incidence of more than 10% in children [1], decreasing to about 3% in the adult population [2]. AD is a chronic disease that can be difficult to control, both due to patient treatment compliance, as well as the unremitting underlying inflammatory process. Moisturizing ointments and topical corticosteroids are the main treatments to minimize dryness and limit inflammation and itchiness in these patients. Recently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast with previous studies that suggested increased Th2 cells because of the association of attention problems with atopic disease, we did not observe an association between attention problems and Th2 cell numbers (Cortese et al., 2018 ; Pelsser et al., 2009 ; Verlaet et al., 2019 ). Previously, it has been shown that in chronic atopic dermatitis immunological inflammation could cause a shift towards increased Th1 and CD8 + T cell numbers (Hijnen et al., 2013 ; Knol and Hijnen, 2016 ). This might explain the association of attention problems with both Th1 and Th2‐mediated disease as well as our study results with increased Th1, CD8 + cells, but not Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with previous studies that suggested increased Th2 cells because of the association of attention problems with atopic disease, we did not observe an association between attention problems and Th2 cell numbers (Cortese et al., 2018 ; Pelsser et al., 2009 ; Verlaet et al., 2019 ). Previously, it has been shown that in chronic atopic dermatitis immunological inflammation could cause a shift towards increased Th1 and CD8 + T cell numbers (Hijnen et al., 2013 ; Knol and Hijnen, 2016 ). This might explain the association of attention problems with both Th1 and Th2‐mediated disease as well as our study results with increased Th1, CD8 + cells, but not Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators may also have a direct bearing on characteristic symptoms; studies have revealed that in AD-associated intractable pruritus-where the receptors involved are often not entirely histaminic 13 -proinflammatory cytokines are prime target suspects that instigate it 14 15 . Naturally brought along with this paradigmatic shift was revamping in management scheme; systemic immunomodulators and biologics have taken a center-stage as an important arsenal against the immunological leg of AD patho-mechanism 16 . The authors, having experienced an apparent, skin barrier-reparative effect with an HS water after 4 weeks of bathing in a tub 17 , were prompted with the question of whether HS water brings upon beneficial effects on cellular and molecular level with certain immune-mediating action.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it has been shown that dupilumab, an antibody blocking IL‐4/IL‐13 receptors, has equal potency in treatment of either extrinsic AD (with increased IgE levels) or intrinsic AD (without increased IgE levels). This can be explained by data showing that Th2 cytokines diminish the expression of barrier proteins such as filaggrin, loricrin, involucrin and antimicrobial peptides . Hence, this illustrates the clinical and immunological diversity of the disease.…”
Section: Introductionmentioning
confidence: 88%
“…This can be explained by data showing that Th2 cytokines diminish the expression of barrier proteins such as filaggrin, loricrin, involucrin and antimicrobial peptides. 34 Hence, this illustrates the clinical and immunological diversity of the disease.…”
Section: Introductionmentioning
confidence: 89%